Rywalizacja irańsko-saudyjska i jej wpływ na stosunki międzynarodowe na Bliskim Wschodzie w XXI wieku - Mruk, Marzena (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Iran and Saudi Arabia are two Middle Eastern countries striving to become regional powers. Relations between Iran and Saudi Arabia since 1979 are based on the rivalry between Shiism and Sunni and on a different approach of states to relations with the United States. Iran’s relations with Saudi Arabia are often called proxy war and have an impact on international relations in the Middle East. The interests of Tehran and Riyadh are currently clashing for example in Syria, Yemen, Bahrain, Iraq and Qatar. The deepening competition between states may in the near future turn into an armed conflict
Keywords: Iran; Saudi Arabia; Middle East; competition